IT auditing : the practitioner's guide to IT audit - Savin, Jerald (Routledge, 2025)
"More than ever, technology is indispensable to business operations and recordkeeping, so people skilled in computer automation-IT auditors-have become an essential part of the financial audit team. This book is a comprehensive guide to the IT audit discipline, and to the impact of abstraction on businesses. Developments including Robotic Process Automation (RPA) and artificial intelligence (AI) mean that businesses are moving from a physical world to an abstracted digital world, increasing reliance on systems, their design, their implementation and on those that oversee and maintain these systems-often parties outside the businesses' control. Though the implications of these shifts go far beyond IT auditing, this book focuses on what IT auditors need to know in this new environment, such as: How to understand abstracted services and appropriate internal business controls How to evaluate situations where physicality has been replaced by abstracted services How to understand and adapt to the impact of abstracted services on objectives, operations, decision-making, and risk management, including changing risk profiles and introducing new risks. In the wake of the CPA Evolution project, this book will be an essential resource for readers seeking Certified Public Accountant (CPA) certification, as well as for business leaders and risk management professionals who need to understand the benefits and challenges of ever-increasing automation and its concurrent abstraction of physical reality"-- Provided by publisher.
Keywords: Information technology -- Auditing.; Information technology -- Management.; elektronické knihy; electronic books